(untitled) (Experimental biology, 2016)
It was studied the effect of chloride, sulfate, carbonate salinity on proline content in the 10-day rice seedlings of domestic and foreign varieties and hybrids at the early stages of ontogenesis. Under salinity stress conditions was revealed 10-fold increase of proline content compared to the control. It was shown that the investigated samples of rice differ by their resistance to salinity in the laboratory conditions. At the chloride, sulfate and carbonate type of salinity free proline accumulation in the varieties cultivated in Kazakhstan: Madina Bakanassky, Kuban 3 and FL 478 (HB 9093) genotype from IRRI had shown good results compared with other samples. As a result of research in all types of salinity (chloride, sulfate and carbonate) high percentage (99-209%) on the accumulation of free proline were characterized next hybrids: ♀Regul x ♂ Kurchanka, ♀Hankaysky429 x ♂ Kurchanka, ♀Marhzan x ♂Kurchanka .